Integrated CAD customization system for fused deposition models in additive manufacture with 3D printing machine. (November 2019) - Achdianto,; Cahyati, Sally; Triyono,; Saifudin,
Abstract: A computerized addictive aided design based on manufacturing system that is digitally integrated, has been modified, built, and designed. The system refers to the smart manufacturing sectoral (smart manufacturing) which to answer the challenges of industrial revolution 4.0, namely the purpose for efficiency of the distance, cost efficiency, time efficiency, quality improvement and increased flexibility. The concept of manufacturing systems with fused deposition modelling 3D printers integrated with the internet or intranet has been modified, for the purpose to connected each other under one platform being namely as category as a Computer Aided Manufacture (CAM) system. A synthesis between the production room and the customer, real-time depiction of 3D CAD users can be presented and connected directly to the manufacturing locations where the desired product is located. Seeing this as an opportunity growing for the industrial society, the author conducted research to modified and collaborate the system. The method used in this study was carried out with rapid application design or better known as Rapid Application Development/RAD aimed at simplifying and accelerating the design of the system for 3D print web application system. CAD drawings can be processed from the user's device to the main webserver and then forwarded into the operator's production system space, resulting in a final product/finished goods, with no restrictions on distance, area and allows low production costs (low production costs). The results of this study represent the manufacturing industrial that is being supported by the application of information technology, where are manufacturing is connected with IoT (Internet of Things). Presenting the benefits of the Industry 4.0 concept. The customization system to be able to add value added for the competitiveness small and medium companies in Indonesia on manufacturing process and can support micro economic growth.